Gibson paradox revisited – liquidity chain effect - Škare, Marinko; Mošnja-Škare, Lorena (Journal of Business Economics and Management, 2014)
Gibson paradox remains a puzzle in the discipline of economics. Previous studies attempted to resolve the paradox looking separately at the gold standard, changing monetary regimes, inflation expectations, risk and uncertainty. Our study shows Gibson paradox holds for the Netherlands 1800-2012 with real long interest rates and prices diverging after 2008. This paper offers empirical evidence (nonlinear cointegration) on the integrity of the Gibson paradox. Single factor cannot explain the paradox itself (because of its nonlinear nature) as previous studies attempted. Empirical link between long interest rates and prices is caused by complex interaction between purchasing power, liquidity, gold prices, market turnover, stocks accumulation, productivity, short-term interest rates. This approach analysis the purchasing power and price relation, resulting in firms’ turnover and liquidity shifts, leading to short-term borrowings changes and pressures on interest rates in the short as well as in long-term. Actually, the model enables us to track the series of price change effects finally resulting in interest rates shifts, via a set of microeconomic and financial laws, which taken at the aggregate level could offer the Gibson paradox explanation. Further studies must explore nonlinear nature of the paradox in order to explain it. Study results have important implications for policy makers and firm governance policy.